Prebiotic Xylo-Oligosaccharides Ameliorate High-Fat-Diet-Induced Hepatic Steatosis in Rats - Sanna Lensu; Raghunath Pariyani; Elina Mäkinen; Baoru Yang; Wisam Saleem; Eveliina Munukka; Maarit Lehti; Anastasiia Driuchina; Jere Linden; Marja Tiirola; Leo Lahti; Satu Pekkala (MDPI, 2022)
Understanding the importance of the gut microbiota (GM) in non-alcoholic fatty liver disease (NAFLD) has raised the hope for therapeutic microbes. We have shown that high hepatic fat content associated with low abundance of Faecalibacterium prausnitzii in humans and, further, the administration of F. prausnitziiprevented NAFLD in mice. Here, we aimed at targeting F. prausnitzii by prebiotic xylo-oligosaccharides (XOS) to treat NAFLD. First, the effect of XOS on F. prausnitzii growth was assessed in vitro. Then, XOS was supplemented or not with high (HFD, 60% of energy from fat) or low (LFD) fat diet for 12 weeks in Wistar rats (n = 10/group). XOS increased F. prausnitzii growth, having only a minor impact on the GM composition. When supplemented with HFD, XOS ameliorated hepatic steatosis. The underlying mechanisms involved enhanced hepatic β-oxidation and mitochondrial respiration. Nuclear magnetic resonance (1H-NMR) analysis of cecal metabolites showed that, compared to the HFD, the LFD group had a healthier cecal short-chain fatty acid profile and on the HFD, XOS reduced cecal isovalerate and tyrosine, metabolites previously linked to NAFLD. Cecal branched-chain fatty acids associated positively and butyrate negatively with hepatic triglycerides. In conclusion, XOS supplementation can ameliorate NAFLD by improving hepatic oxidative metabolism and affecting GM.